2008
DOI: 10.1364/ol.33.000198
|View full text |Cite
|
Sign up to set email alerts
|

Spiraling multivortex solitons in nonlocal nonlinear media

Abstract: We demonstrate the existence of a broad class of higher-order rotating spatial solitons in nonlocal nonlinear media. We employ the generalized Hermite-Laguerre-Gaussian ansatz for constructing multivortex soliton solutions and study numerically their dynamics and stability. We discuss in detail the tripole soliton carrying two spiraling phase dislocations, or self-trapped optical vortices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 23 publications
0
59
1
Order By: Relevance
“…Rotating high-order LG beams have been studied in the past by superposing beams with multiple and non-circularly symmetric phase dislocations about the optical axis [16]. Moreover, Hermite-LaguerreGaussian modes or multi-vortex solitons have been reported to rotate as they propagate in non-linear media [17,18]. In contrast to these previous works, the optical twister has a single phase-dislocation along the optical axis with phase and amplitude profile spiraling as the beam propagates in free space.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating high-order LG beams have been studied in the past by superposing beams with multiple and non-circularly symmetric phase dislocations about the optical axis [16]. Moreover, Hermite-LaguerreGaussian modes or multi-vortex solitons have been reported to rotate as they propagate in non-linear media [17,18]. In contrast to these previous works, the optical twister has a single phase-dislocation along the optical axis with phase and amplitude profile spiraling as the beam propagates in free space.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of an optical beam in a nonlocal nonlinear medium in the paraxial approximation is described by NNLSE [3]:…”
Section: The Moments Methods Analysismentioning
confidence: 99%
“…Many novel features of the nonlocal nonlinearity such as the suppression of collapse [1] and the support of vortex solitons [2,3] have been found. In strongly nonlocal nonlinear (SNN) media, the characteristic length of the material response function is much larger than the beam width.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the nonlocality can prevent the collapse of self-focusing beams in media with cubic nonlinearity [14], suppress azimuthal instabilities of vortex solitons [15], and stabilize Laguerre soliton clusters, azimuthons, and multipole solitons [12]. The evolution of optical beams in nonlocal nonlinear media is governed by the nonlocal nonlinear Schrödinger (NNS) equation [12,16].…”
Section: I Introductionmentioning
confidence: 99%